Reconstitution of humoral immunity and decreased risk of infections in patients with chronic lymphocytic leukemia treated with Bruton tyrosine kinase inhibitors. Issue 10 (23rd August 2020) - Pleyer, Christopher; Sun, Clare; Desai, Sanjal; Ahn, Inhye E.; Tian, Xin; Nierman, Pia; Soto, Susan; Superata, Jeanine; Valdez, Janet; Lotter, Jennifer; Wiestner, Adrian
Abstract: Immune dysregulation in chronic lymphocytic leukemia (CLL) contributes to a high rate of infections and morbidity. The Bruton tyrosine kinase (BTK) inhibitors ibrutinib and acalabrutinib mark major breakthroughs in the treatment of CLL, however many patients require long-term therapy with these agents. Despite receiving effective therapy for CLL, patients on BTK inhibitors remain immunocompromised and at risk of infectious complications. We previously reported that treatment of CLL with ibrutinib leads to partial reconstitution of humoral immunity and fewer infections during the first two years of therapy. It is currently unclear whether the positive effects of ibrutinib on the immune system are sustained during long-term therapy. Acalabrutinib is a newer, more selective BTK inhibitor than ibrutinib; however a detailed evaluation of the immunologic impact of acalabrutinib therapy is lacking. Herein, utilizing two independent trials, we assessed the immunological effects and infectious risk of ibrutinib and acalabrutinib treatment in patients with CLL.